CTNNBIP1 downregulation is associated with tumor grade and viral infections in gastric adenocarcinoma. Issue 3 (4th August 2018) - Kosari‐Monfared, Mohadeseh; Nikbakhsh, Novin; Fattahi, Sadegh; Ghadami, Elham; Ranaei, Mohammad; Taheri, Hassan; Amjadi‐Moheb, Fatemeh; Godazandeh, Gholam A.; Shafaei, Shahryar; Pilehchian‐Langroudi, Maryam; Samadani, Ali Akbar; Akhavan‐Niaki, Haleh
Abstract : Gastric cancer is a life‐threatening disease; resulting from interaction among genetic, epigenetic, and environmental factors. Aberrant dysregulation and methylation changes in Wnt/β‐catenin signaling downstream elements are a prevalent phenomenon encountered in gastric tumorigenesis. Also, viral infections play a role in gastric cancer development. CTNNBIP1 (β‐catenin interacting protein 1) gene is an antagonist of Wnt signaling which binds to the β‐catenin molecules. The CTNNBIP1 function as tumor suppressor gene or oncogene in different types of cancer is controversial. Moreover, its function and regulatory mechanisms in gastric cancer progression is unknown. In the present study, we examined CTNNBIP1 gene expression, the methylation status of the regulatory region of the gene, and their association with Epstein–Barr virus (EBV), and cytomegalovirus (CMV) and Helicobacter pylori infections in human gastric adenocarcinoma tissues in comparison with their adjacent nontumoral tissues. Our data revealed a significant downregulation of CTNNBIP1 in gastric tumors. Female patients showed lower level of CTNNBIP1 than males ( p  < 0.05). Also, decreased expression of CTNNBIP1 was markedly associated with well‐differentiated tumor grades ( p  < 0.05). No methylation change was observed between tumoral and nontumoral tissues. Additionally, CTNNBIP1 down regulation was significantly associated with CMV infection ( p  < 0.05). In the absence of EBV infection, lower expression of CTNNBIP1 was observed. There was no association between H. pylori infection and CTNNBIP1 expression. Our findings revealed the tumor suppressor role for CTNNBIP1 in gastric adenocarcinoma. Interestingly, EBV and CMV infections modulate CTNNBIP1 expression. Abstract : An image which choose a graphical illustration in the abstract of the article. Aberrant dysregulation and methylation changes of Wnt/β‐catenin signaling downstream elements are prevalent phenomenon encountered in gastric tumorigenesis. Also, viral infections play a role in gastric cancer development. CTNNBIP1 (β‐catenin interacting protein 1) gene is an antagonist of Wnt signaling which binds to the β‐catenin molecules. Our findings revealed a tumor suppressor role for CTNNBIP1 in gastric adenocarcinoma. Interestingly, Epstein–Barr virus and CMV infections modulate CTNNBIP1 expression.